The Identification of Growth Centers and Spatial Autocorrelation in East Kalimantan Province - Faiq, Gandhika Tri; Gunawan, Diah Setyorini (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
In 2013 and 2023, East Kalimantan Province had the highest GRDP in Kalimantan Island. However, based on the Williamson Index, the level of income distribution that occurs between districts/cities is still low. This study aims to identify growth centers and spatial interactions of districts/cities in East Kalimantan Province in 2013 and 2023. The research method uses scalogram analysis, centrality index and gravity analysis. The results showed that in 2013 there were 1 district/city in Hierarchy I, 3 districts/cities in Hierarchy II, 2 districts/cities in Hierarchy III and 4 districts/cities in Hierarchy IV. In 2023 there are 3 districts/cities in Hierarchy I, 4 districts/cities in Hierarchy II, 3 districts/cities in Hierarchy III and 1 district/city in Hierarchy IV. From 2013 to 2023 the interaction between growth centers and their hinterland areas increased. Samarinda City, Balikpapan City, and East Kutai District are the regions that have the strongest interaction. The policy implication is that economic cooperation between the growth center and its hinterland regions is needed so that economic growth can be helped in each region.